An Application of the Localization Strategy of MNCs in China: The case of Starbucks - GU, YIFAN (2017)
With the rise of the Chinese market, more MNCs begin to take China as the main market. In order to take up more market share in China, choosing a feasible business strategy is vital for MNCs. Localization strategy is now considered as one of the most suitable strategies in China. However, the motivations and impacts of localization strategy and its enlightenments for western catering multinationals in China are rarely researched. Therefore, I set Starbucks as a case study to do an in-depth analysis of localization strategy in China on the basis of overseas direct investment theory and strategic management theory. The finding shows that Starbucks take localization as the main strategy is because of both internal (company) and external (host country) factors. Correspondingly, the impacts of localization reflect in Starbucks performance and China’s transformation. Still, there is the limitation in this research. For instance, Starbucks has its own distinctive characteristics which are difficult to imitate. Thus, setting Starbucks as a single case study is not comprehensive and the research findings cannot be applied to all catering multinationals. Also, it is hard to say that localization strategy is suitable for all MNCs in China.